2010
DOI: 10.1111/j.1600-079x.2009.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of melatonin on nicotine-induced vasculopathy

Abstract: Tobacco smoking is responsible for death of many people each year and increases the risk of developing numerous disorders, particularly cardiovascular disease and cancer. Among the components of cigarette smoke, nicotine is known to excert proatherosclerotic, prothrombotic and proangiogenic effects on vascular endothelial cells. The current study was designed to investigate the mechanisms by which nicotine induces endothelial dysfunction and further to examine whether melatonin protects against nicotine-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…ICAM-1/VCAM-1 are principle modulators for the stable adhesion of leukocytes, including neutrophils and lymphocytes in alveolar epithelial cells [43]. Rodella et al [44] discovered marked elevation in VCAM-1 expression upon NIC treatment in vitro and in vivo respectively. Data of the existing study demonstrated that NIC treated animals had marked elevation in VCAM-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1/VCAM-1 are principle modulators for the stable adhesion of leukocytes, including neutrophils and lymphocytes in alveolar epithelial cells [43]. Rodella et al [44] discovered marked elevation in VCAM-1 expression upon NIC treatment in vitro and in vivo respectively. Data of the existing study demonstrated that NIC treated animals had marked elevation in VCAM-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…36,37) Melatonin was shown to block ICAM-1 release in a variety of studies that investigated its vascular effects. 37,38) Potential neurological and neuropsychological complications following cardiac surgery are categorised into two major groups. Type 1 complications (with an incidence of 3%-6%) include death due to stroke or hypoxic encephalopathy, non-fatal incident stroke, transient ischaemic attack, stupor and coma.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, there had been preconditions typical of chronic nicotine intoxication, which lead to hypertension and atherosclerosis. A long-term (28 days) combined of МТ (5 mg/kg) along with nicotine, however, prevented the side effects of smoking [71].…”
mentioning
confidence: 99%